Midgut Volvulus Due to a True Jejunal Diverticula - Melissa Kyriakos Saad (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Jejunal diverticula is a rare condition quoted to affect between 0.5% and 7% of the individuals. This disease is usually clinically silent but becomes symptomatic when complications develop. Among its complications is small bowel volvulus that is a very rare entity.